2019
DOI: 10.1007/978-3-030-16892-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Why Mathematics Is Valuable for Turkish, Turkish Immigrant and German Students? A Cross-Cultural Study

Abstract: This study investigated students' views regarding the value of mathematics. It reports on a smaller part of findings from a wider comparative study concerning student values of mathematics and mathematics education that belonged to Turkish students in Turkey, Turkish immigrant students in Germany, and German students in Germany. Students were in Grade 9 (14-15 years old) and the data was gathered through semi-structured interviews, and analyzed using the constant comparative method. The results revealed four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
3
16
0
3
Order By: Relevance
“…This result shows that students still cannot give up traditional teaching methods, although ICT has been gradually incorporated into the day-to-day mathematics teaching and learning activities in educational settings in Turkey. Similarly, the results of a recent qualitative study of Dede (2019) with ninth-grade students were also partially like those of Dede and Barkatsas (2019). Accordingly, the students' mathematics values are gathered in four main categories: practice, relevance, rationalism, and fun.…”
Section: Mathematics Values In High Schools In Turkeymentioning
confidence: 87%
See 3 more Smart Citations
“…This result shows that students still cannot give up traditional teaching methods, although ICT has been gradually incorporated into the day-to-day mathematics teaching and learning activities in educational settings in Turkey. Similarly, the results of a recent qualitative study of Dede (2019) with ninth-grade students were also partially like those of Dede and Barkatsas (2019). Accordingly, the students' mathematics values are gathered in four main categories: practice, relevance, rationalism, and fun.…”
Section: Mathematics Values In High Schools In Turkeymentioning
confidence: 87%
“…Semantic content analysis is the process of creating subcategories to detect themes in a text or phenomenon (Tavşancıl & Aslan, 2001). In this sense, the EBA contents reviewed were analysed based on the values and value signals that emerged in the literature (for example, Bishop, 1988;Dede, 2012Dede, , 2015Dede, , 2019Dede & Barkatsas, 2019;Lim & Ernest, 1997;Seah, 1999Seah, , 2011. As mentioned above, the general educational values have not been analysed in the current study since they do not directly affect students' mathematics achievement (Seah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Values vary substantially by country and cultural characteristics. For example, a study of Swedish students suggested that accomplishment and cognitive factors (e.g., knowing the 6 ECNU Review of Education timetables and mathematical understanding) and teacher support were most important (Andersson et al, 2019;Ö sterling et al, 2015), whereas German and Turkish students valued mathematical accomplishment (e.g., test preparation/performance), meaningful learning (e.g., real-world applications, future career, and applicability), engaging mathematics lessons (e.g., puzzles/games), and mathematical understanding and skills (Dede, 2019). In Ghana, students reported valuing accomplishment (e.g., mastery, achievement, and accuracy), meaning (e.g., relevance), mathematical cognitions (e.g., mathematical strategies and fluency), and technology (e.g., calculators).…”
Section: Values and Valuing In Mathematics Educationmentioning
confidence: 99%